Actualizarea reperelor normative naționale inerente statului social [Articol] - Guceac, Ion (CEP USM, 2024)
The article describes some important aspects of the scientific and normative benchmarks of the welfare state. The opportunity of approaching this topic is determined not only by the absence of the concept of the social state as a legal category in the legal literature of the Republic of Moldova, but also by the need for normative enshrinement of favorable conditions for the full development of citizens’ personality, rights, and equal opportunities. In this context, it is noted that the imperative of the social state consists of goals and objectives that ensure, in fact, the welfare of people, peace and social equity, as well as guarantee the protection of human rights and freedoms and citizens. The social state can only be considered to be a state which ensures a robust social policy geared to securing the rights, freedoms, and interests of individuals. In recognition of the fact that in the Republic of Moldova, the formation of the social state is at an initial stage, it is proposed to develop a Concept of the Social State.

Articolul prezintă descrierea unor aspecte importante privind reperele doctrinaire și normative ale statului social. Oportunitatea abordării acestui subiect este determinată nu doar de de absența conceptului statului social ca o categorie juridică în literatura juridică din Republica Moldova, dar și de necesitatea consacrării normative a unor condiții favorabile pentru dezvoltarea deplină a personalității cetățenilor, drepturilor și, șanselor lor egale. În acest context, se constată că imperativul statului social consistă în scopuri și obiective care asigură, de fapt, bunăstarea oamenilor, pacea și echitatea socială, garantează protecția drepturilor și libertăților omului și cetățeanului. Social poate fi considerat numai statul care asigură o politică socială robustă, orientată spre asigurarea drepturilor, libertăților și intereselor indivizilor. Pornind de la recunoașterea faptului că în Republica Moldova, formarea statului social se află la etapa inițială, se propune elaborării unei Concepții a statului social.
UPDATING NATIONAL REGULATORY MILESTONES INHERENT IN THE WELFARE STATE
Keywords: social state; justice; equity; welfare; rights; freedoms; social function; social policies; social rights; stat social; justiție; echitate; bunăstare; drepturi; libertăți; funcție socială; politici sociale; drepturi sociale